Mass and lifetime measurements at the experimental storage ring of GSI - Bosch, Fritz; Litvinov, Yuri A. (International journal of mass spectrometry, 2013)
Precision mass and β-lifetime measurements conducted at the experimental storage ring ESR in Darmstadt are reviewed. Relativistic radioactive isotopes can be produced by projectile fragmentation and fission reactions, separated in flight by the fragment separator FRS, and injected into the cooler-storage ring ESR. This powerful experimental method gives access to all fragments with half-lives down to the sub-millisecond range. The research potential is demonstrated by several examples of precision mass and lifetime measurements. A particular emphasis is given to the worldwide unique experimental program at the ESR on the studies of bound-state β− decay.